Preliminary Epidemiological Investigation of COVID-19 Pandemic in Alassabiea City, Libya - Mahmoud, Abdusalam S.; Swesi, Abdulfatah R.; Abeed, Ali A.; Elbaz, Abdulkareem K. (Journal of Medical Sciences, 2023)
Background: The Coronavirus Severe Acute Respiratory Syndrome-2 (SARS CoV-2) was reported as sporadic outbreaks for the first time last December 2019 in Wuhan, Hubei Province, China. Later, spillover across China with transboundary spread worldwide, and due to quickly raising the epidemic curve with a high case fatality rate (CFR), on 11 March 2020, WHO announced the coronavirus outbreak as a pandemic. Material and Methods: The cross-sectional study was conducted to investigate the epidemiological situation of COVID-19 and study the risk factors associated with infection in the city of Alassabiea from July 2020 to March 2021, a total of 1542 respiratory samples specimens (nasopharyngeal swabs) were screened by real-time RT-PCR test for detection of SARS-CoV-2. Results: The overall infection rate of COVID-19 was estimated to be (15.63%; 241/1542) with a 95% confidence interval (CI) (13.94-17.58%). The results showed a significant difference (P=.005) in COVID.19 infection rates among age groups. Conclusion: The epidemiological situation of the SARS-CoV-2 was underestimated during the first wave of the COVID-19 pandemic; however, our results reported a high infection rate of COVID-19 in Alassabiea city due to cultural and social lifestyles in this city. Potentially, the weakness of quarantine measures and shortage of healthy capacity have made it difficult to communicate between the health sectors. Therefore, the Libyan National Centre for Disease Control (NCDC) under the supervision of Libyan healthy authorities should enforce the public health capacity and the surveillance system including training surveillance officers and Laboratory technicians.